Analisis penanaman sikap profil pelajar pancasila dimensi berkebhinekaan global pada pembelajaran ipas kelas iv di sekolah dasar - Rendita Fairuz Nabila Darmawan; Siti Istiyati Istiyati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2024)
This research aims to find out (1) how to instill a Pancasila student profile attitude with global diversity in fourth grade natural and social science learning at the state elementary school  (2) the results of its instillation. The type of approach in this research is descriptive qualitative. The subjects of this research were teachers and students of fourth class at the state elementary school of . Data collection techniques use the results of observations, interviews & document studies. Test the validity of the data using source triangulation and technique triangulation. The data analysis technique uses Miles and Huberman analysis. The results of the research show: (1) The method used by teachers by giving examples shows 80% results and can be categorized as good, the method with habit shows 100% results and can be categorized as very good and the method with spontaneous activities shows 80% results and can be categorized as very good. (2) The results of cultivating this attitude can be seen from the large number of students who fulfill the elements of the global diversity dimension. Instilling this attitude, namely by providing examples, shows that 80% of the results are categorized as good. For the habituation method, 71% of the results were categorized as good. For the third method with spontaneous activities, 67% of the results were categorized as good. Based on the research results, it can be concluded that the method instilled by the teacher can be categorized as good and the results of instillation using this method are also categorized as good